2008
DOI: 10.1002/hfm.20109
|View full text |Cite
|
Sign up to set email alerts
|

Interventions in the construction industry: A systematic review and critical appraisal

Abstract: Musculoskeletal disorders (MSD) in the construction industry represent a significant problem resulting in days away from work, and the effective solution to this problem requires the implementation of useful interventions. This article presents a systematic review and critical appraisal of construction intervention studies to provide a basis for future research and practice. A comprehensive search of seven electronic databases-Medline, PubMed, Ergonomics Abstracts, Health and Safety Science Abstracts, BIOSIS, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Researchers and ergonomists have recommended the development of trade-specific tools to reduce the risk of work-related MSDs in the construction industry (Rinder, et al, 2008;Li, 2002). However, our analysis suggests that there may not be a 'one size fits all' solution to tool selection.…”
Section: Implications For Tool Selection and Designmentioning
confidence: 79%
“…Researchers and ergonomists have recommended the development of trade-specific tools to reduce the risk of work-related MSDs in the construction industry (Rinder, et al, 2008;Li, 2002). However, our analysis suggests that there may not be a 'one size fits all' solution to tool selection.…”
Section: Implications For Tool Selection and Designmentioning
confidence: 79%
“…Consequently, a reduction of the physical workload to promote sustainable working careers [8] in construction work should have high priority. Moreover, a systematic review highlighted an urgent need for interventions focusing on reducing WMSD in construction workers [9]. In addition, most studies are based on self-reported measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Rates of musculoskeletal disorders (MSD) in construction are responsible for high rates of both workers’ compensation claims and personal health claims [CPWR—The Center for Construction Research and Training, ; Dale et al, ; Lipscomb et al, ,] and implementation of sustainable ergonomic solutions to prevent MSD in construction work is a challenge [Schneider, ; Hecker et al, ; Hess et al, ; Weinstein et al, ; Rinder et al, ; Kramer et al, ]. An ergonomic solution is defined as an available new device or technology that can be used to reduce musculoskeletal disorder (MSD) risk factors in construction related tasks, and may include equipment, positioners, hand tools, power tools, manual material handling devices (MMH), and personal protective equipment (PPE) [Bernard, ; Dale et al, ].…”
Section: Introductionmentioning
confidence: 99%